Investigating progestin-mediated crosstalk between the androgen receptor and estrogen receptor subtypes in breast cancer cell lines - Brink, Danielle (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.